FEMINIST RESPONSES TO CRISES AND DEHUMANIZATION transnational scholar. (ROUTLEDGE, 2026)
Feminist Responses to Crises and Dehumanization brings together academic knowledge with activist strategies and lived experiences from different socio-geographic angles--bridging the gap between theory and on-the-ground impact.The experience of the Covid-19 pandemic has laid bare humanity's existential vulnerabilities. But ecological, economic, political, reproductive, and other instabilities have also shown us how we are connected to non-human species and planet Earth, and how human practices that have long normalized devaluation have in fact created the contemporary multi-crisis. In response to this historical moment, this book articulates visions toward fairer, more caring, and sustainable societies. It brings together feminist and queer scholars and scholar-activists from different world regions who write about critical crisis issues, offer reinterpretations of these crises and develop strategies of resistance. The contributions focus on three dimensions of crisis-ecological devastation and economic exploitation; political authoritarianism and violence; and the denial of reproductive justice and bodily autonomy-and combine systemic and situated analysis with a focus on agency.This volume will appeal to scholars and students interested in transnational feminism, in areas such as Gender Studies, Political Science, Social Studies, and International Relations.